História oral de vida de professores da área da saúde de cursos particulares de nível técnico de Santa Maria/RS - Silva, Suzel Lima da (2021)
For this research, the current scenario of education in Brazil was taken into account, in which studies converge on improvements in teaching, aimed at innovations in teaching practices. Some institutions are beginning to value the teacher's individual knowledge, and such changes, by the managers of the private network, present reflections and discussions added to innovative pedagogical practices. In the context of Professional and Technological Education (EPT), reflections are made on the direct relationships that experiences and experiences acquired throughout professional life can define the current situation of the subject who is a teacher, working in institutions with this profile. It started, then, from the perspective facing the lack of training for teaching at EPT, as well as the non-obligation of graduation training to exercise this role. Considering the above, the research aimed to investigate how the training of teachers from private technical schools working in technical courses in the area of health occurs. And, through this deepening in life histories, it was possible to discuss the trajectory of teacher education, verifying what they identify as professional teacher achievement. As for the methodological aspects, a qualitative approach research was carried out, using the Oral History of Life (HOV) method by Meihy and Holanda (2007) and, for data analysis, the Textual Discursive Analysis of Moraes and Galiazzi (2006), was the adopted reference. The research collaborators were four professors who work in health courses in the private network of the EPT in Santa Maria/RS. Due to the Covid-19 pandemic, the interviews took place in a virtual environment, from where the collaborators narrated their professional and teacher training trajectories at the EPT. The research findings reinforce the weaknesses of the training processes of health professionals for the teaching career, from which all collaborators reported having developed the pedagogical practice through mistakes and successes in the classroom. The training acquired along the trajectories, are added to the context of a new policy in the EPT, from which pedagogical training is required for all members of the teaching staff of technical schools. From such experiences, among the pedagogical strategies that reaffirm the important role of teachers without initial pedagogical training, there is the example of clinical experiences in order to better exemplify the theories worked in the classroom, justifying the fact of maintaining the concomitant professional practice with teaching. In this threshold, there is the desire to qualify the professional profile of the professional classes of each one, because for all collaborators, the recognition of failures in their training processes was recurrent. It is concluded that the research achieved its objective of generating self-reflection, revealing the necessary investment in continuing education with a focus on the development of pedagogical practices in EPT.